2015
DOI: 10.1142/9753
|View full text |Cite
|
Sign up to set email alerts
|

School Mathematics Textbooks in China

Abstract: Let µ and ν be two probability measures on R d , where µ(dx) = e −V (x) dx R d e −V (x) dx for some V ∈ C 1 (R d ). Explicit sufficient conditions on V and ν are presented such that µ * ν satisfies the log-Sobolev, Poincaré and super Poincaré inequalities. In particular, if V (x) = λ|x| 2 for some λ > 0 and ν(e λθ|•| 2 ) < ∞ for some θ > 1, then µ * ν satisfies the log-Sobolev inequality. This improves and extends the recent results on the log-Sobolev inequality derived in [20] for convolutions of the Gaussian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 1,218 publications
1
20
0
Order By: Relevance
“…In order to support the theoretical research of the three-ring teaching method, the empirical method is used to study the use value of the three-ring teaching method in the subject teaching of vocational colleges, and the influence of the three-ring teaching method on students' learning subjectivity is verified [5].…”
Section: Experimental Purposementioning
confidence: 99%
“…In order to support the theoretical research of the three-ring teaching method, the empirical method is used to study the use value of the three-ring teaching method in the subject teaching of vocational colleges, and the influence of the three-ring teaching method on students' learning subjectivity is verified [5].…”
Section: Experimental Purposementioning
confidence: 99%
“…In this section, we provided a brief review of the essential role that learning dispositions play in college students' learning process. Mindful agency is positively correlated with academic emotion (Q. Wang & Zhang, 2016), learning strategy regulation abilities (Q. Wang & Ar, 2016), and creativity on the dimension of fluency and originality (Q. Wang & Hu, 2016). Mindful agency predicted positively a deep approach to learning through the mediator of need for cognition (Q. Wang & Pan, 2018) and negatively academic procrastination (Q. Wang & Yu, 2016) and test anxiety (Q. Wang & Zhang, 2016).…”
Section: Importance Of Learning Dispositions For College Studentsmentioning
confidence: 99%
“…Mindful agency is positively correlated with academic emotion (Q. Wang & Zhang, 2016), learning strategy regulation abilities (Q. Wang & Ar, 2016), and creativity on the dimension of fluency and originality (Q. Wang & Hu, 2016). Mindful agency predicted positively a deep approach to learning through the mediator of need for cognition (Q. Wang & Pan, 2018) and negatively academic procrastination (Q. Wang & Yu, 2016) and test anxiety (Q. Wang & Zhang, 2016). A recent intervention study reported that improvement in mindful agency mediates the changes in self‐efficacy, emotional intelligence, and meta‐cognition after coaching (Peng & Wang, 2020).…”
Section: Importance Of Learning Dispositions For College Studentsmentioning
confidence: 99%
“…Compared with the traditional CRC algorithm, the table look-up method CRC algorithm [6] used in this paper has more efficient calculation efficiency while taking into account the detection ability. Data encryption algorithms are divided into three categories: symmetric encryption, asymmetric encryption and hybrid encryption [7][8][9]. The confidential algorithm TEA used in this paper aims to achieve maximum encryption and decryption speed while occupying the minimum memory [10].…”
Section: Introductionmentioning
confidence: 99%